Sensory Evaluation of Smoked Sardine Coated With Local Spices - Nurufairah Uslee; Mohd Azrie Awang (Universiti Malaysia Sabah, 2024)
Sardines refer to a group of fish from the Clupeidae family, including the genera Sardinella, Amblygaster, Decapterus, or Cetengraulis. The sensory evaluation of smoked sardines coated with local spices in this study involved the use of liquid smoke immersion. The study aimed to formulate the best-smoked fish coated with local spices, resulting in seven formulations: the control, F1, F2, F3, F4, F5, and F6. These formulations were immersed in liquid smoke and coated with varying percentages of three main spices: ginger, garlic, and dried chili. Based on sensory analysis with 50 panelists, it was concluded that F5, with 6% liquid smoke, emerged as the optimal formulation.